Investigation of SIP Signaling Messages Servicing Time - Jarutis, A.; Gedmantas, R.; Grimaila, V. (Elektronika ir Elektrotechnika, 2011)
SIP is most widely used signaling protocol in IP telephony for communication sessions conclusion. At time of providing voice services, this communications protocol messages fall to specialized network nodes. Service quality depends on their serving at nodes. To assess the temporal characteristics of services, it is necessary to know the signaling message average handling times values of possible deviations of distribution. In this work experimentally were determined statistical handling time characteristics of individual messages and total message flow traffic entering the SIP, PS, AS and DB MRF nodes. It was found that the service times of messages in the form of their distribution are close to normal. However, the hypothesis that the experimentally obtained distribution is normal was rejected by the 2criterion of verification. Therefore in the SIP signaling components analytical studies is proposed to use a general distribution. Ill. 4, bibl. 11, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.692